Changes in plasma phospholipid fatty acid profiles over 13 years and correlates of change: European Prospective Investigation into Cancer and Nutrition-Norfolk Study. Issue 6 (17th April 2019) - Zheng, Ju-Sheng; Imamura, Fumiaki; Sharp, Stephen J; Koulman, Albert; Griffin, Julian L; Mulligan, Angela A; Luben, Robert; Khaw, Kay-Tee; Wareham, Nicholas J; Forouhi, Nita G
ABSTRACT: Background: Little is known about changes in blood fatty acid compositions over time and the correlates of any changes in a general population. Objective: The aim of this study was to estimate changes in 27 individual plasma phospholipid fatty acids and fatty acid groups over time, and to identify potential correlates of these changes. Methods: Plasma phospholipid fatty acids were profiled at 3 time-points (1993–1997, 1998–2000, 2004–2011) among 722 participants in the European Prospective Investigation into Cancer and Nutrition-Norfolk Study, UK. Linear regression models were used to estimate both 1 ) mean changes over time in 27 individual fatty acids and 8 prespecified fatty acid groups and 2 ) associations of changes in dietary and lifestyle factors with changes in the 8 fatty acid groups, mutually adjusted for dietary/lifestyle factors and other confounders. The prespecified fatty acid groups were odd-chain saturated fatty acids (SFAs), even-chain SFAs, very-long-chain SFAs, marine n–3 polyunsaturated fatty acids (PUFAs), plant n–3 PUFA, n–6 PUFAs, monounsaturated fatty acids (MUFAs), and trans-fatty acids (TFAs). Results: Adjusted for confounders, fatty acid concentrations decreased for odd-chain SFAs (annual percentage difference in mol percentage: −0.63%), even-chain SFAs (−0.05%), n–6 PUFAs (−0.25%), and TFAs (−7.84%). In contrast, concentrations increased for marine n–3 PUFAs (1.28%) and MUFAs (0.45%), but there were no changes in very-long-chain SFAs or plant n–3 PUFA. Changes in fatty acid levels were associated with consumption of different food groups. For example, a mean 100 g/d increase in fatty fish intake was associated with a 19.3% greater annual increase in marine n–3 PUFAs. Conclusions: Even-chain SFAs and TFAs declined and marine n–3 PUFAs increased over time. These changes were partially explained by changes in dietary habits, and could potentially help interpret associations of baseline fatty acid composition with future disease risk.